Implementasi Mikoriza sebagai Sarana Pengetahuan Konservasi Mandiri Lahan Marginal di Kecamatan Kabuh Kabupaten Jombang - Ambar Susanti; Rohmat Hidayat; Hari Prasetjono (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2018)
The purpose of training of mycorrhizalas biological agents, conducted in Tanjungwadung village, District of Kabuh, Jombang, 30 July to 23 August 2017, is to liaisefarmers to academic factsin order to convey actual information and to discuss aboutmycorrhiza. The benefits of this activity relates to agriculture education for farmers to increasesoil fertility with the application of mycorrhizal as a biological agents’ fertilizer, to become oneof the solution to the problem of dependence on chemical fertilizers. The methods ofagricultural discussions and demonstrations of mycorrhizal propagation with appropriatetechnology can be done by farmers in the field. The questionnaire to the trainees wasconducted as a form of evaluation to the farmers’ knowledge after receiving the training.Based on the results, 1) pre-test results on pests and diseases in tobacco and onion crops,ranged 60%, and increased 80% during post test; 2) knowledge of synthetic chemical fertilizerduring pre-test averaging 40%, and post test 70%, while 3) pretest about mycorrhiza onlyabout 20%, and post-test 40%. The training participants are capable of practicing the way ofmycorrhizal propagation with the appropriate production technology of MycorrhizalArbuscularVascular (MAV) that can be done by the farmers in the marginal land.